Social Capital Transformation in the Digital Era: A Study of the Shift in Social Interactions of Indonesian Youth - Muhammad Faisal; Romi Mesra (PT. NALURI EDUKASI PRESS, 2024)
This study aims to analyze the transformation of social capital among young Indonesians in the context of digitalization, focusing on changes in social interaction patterns, the formation of digital social capital, and its implications for socio-cultural development. Using a qualitative approach with a systematic literature study method, this study analyzes scientific articles published in the period 2019-2024 from the Scopus, Web of Science, and Google Scholar databases. The results of the study indicate that digital transformation has created a new form of social capital that is more dynamic and flexible, with 80% of social interactions of young Indonesians now taking place in digital spaces. Digital platforms facilitate the formation of broader and more diverse social networks, but also create challenges in terms of the digital divide and the development of social skills. The study recommends the development of an integrative framework to understand and facilitate the formation of effective digital social capital, as well as strategies to balance digital and physical interactions. Policies are also needed that can address the digital divide and support the development of digital social skills among young Indonesians.